2021
DOI: 10.1002/dc.24728
|View full text |Cite
|
Sign up to set email alerts
|

Review of the cytological features of olfactory neuroblastoma: A retrospective single‐center study

Abstract: Olfactory neuroblastoma (ONB) is a rare malignant neuroectodermal tumor. Due to the rarity, there are scarce reports describing the cytological features of ONB. Thus, we aimed to analyze these cytological features and discuss their differences depending on the histological grading of ONB. Patients with a histopathological diagnosis of ONB who underwent fine‐needle aspiration cytology were enrolled in the study. The cytological features, including arrangement and shape of neoplastic cells, nuclear features, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 9 publications
1
5
1
Order By: Relevance
“…A two-cell pattern of viable and apoptotic cells described in some ONBs and found to correlate with high tumor grade is also a non-specific finding reflective of high proliferation of tumor cells, and has been reported in other tumors of neuroendocrine/neuroectodermal origin in the head and neck. 5 We identified this feature in half the aspirates in our study, and found no correlation with Hyams grade. Another noteworthy documented feature is 'paranuclear blue bodies' which are dark blue cytoplasmic globules indenting the nucleus, initially described in small cell carcinoma and subsequently in other small round cell tumors like ONB.…”
Section: Resultscontrasting
confidence: 53%
See 4 more Smart Citations
“…A two-cell pattern of viable and apoptotic cells described in some ONBs and found to correlate with high tumor grade is also a non-specific finding reflective of high proliferation of tumor cells, and has been reported in other tumors of neuroendocrine/neuroectodermal origin in the head and neck. 5 We identified this feature in half the aspirates in our study, and found no correlation with Hyams grade. Another noteworthy documented feature is 'paranuclear blue bodies' which are dark blue cytoplasmic globules indenting the nucleus, initially described in small cell carcinoma and subsequently in other small round cell tumors like ONB.…”
Section: Resultscontrasting
confidence: 53%
“…Another noteworthy documented feature is 'paranuclear blue bodies' which are dark blue cytoplasmic globules indenting the nucleus, initially described in small cell carcinoma and subsequently in other small round cell tumors like ONB. 5 However, we did not identify them in any of the cases in this series. Mitotic fig-…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations